Dampak Metode Struktural Analitik Sintetik (SAS) dan Dukungan Orang Tua terhadap Kemampuan Calistung Siswa SD - Irene Milenia Siki; Imam Suyitno; Ade Eka Anggraini; Eddy Sutadji; Sri Rahayuningsih (Universitas Negeri Malang, 2024)
The lack of research on the impact of the SAS method and parental support on the literacy skills of elementary school students is the background of this study. Literacy skills are the basis that must be possessed by students to support further understanding. The purpose of the study was to determine the impact of the SAS method and parents in improving literacy skills. The research used databases, namely open knowledge maps, publish or perish, and google scholar. Data collection refers to the PRISMA diagram. Out of 600 articles, 34 articles were used in the research. The data analysis technique was descriptive qualitative. The results showed that the SAS method forms the basis of literacy, increases learning motivation, and advances students' visual and numerical abilities. Parents' role in providing a learning environment encourages students' reading habits. The combination of the SAS method at school and parents significantly improved students' literacy skills. Minimnya penelitian tentang dampak metode SAS dan dukungan orang tua terhadap kemampuan calistung siswa SD melatarbelakangi penelitian ini. Kemampuan calistung menjadi dasar yang harus dimiliki oleh siswa untuk mendukung pemahaman lebih lanjut. Tujuan penelitian untuk mengetahui dampak metode SAS dan orang tua dalam meningkatkan kemampuan calistung. Penelitian menggunakan database, yakni openknowledge maps, publish or perish, dan google scholar. Pengumpulan data mengacu pada diagram PRISMA. Dari 600 artikel, 34 artikel digunakan dalam penelitian. Teknik analisis data berupa deskriptif kualitatif. Hasil penelitian menunjukkan metode SAS membentuk dasar literasi, meningkatkan motivasi belajar, dan memajukan kemampuan visual serta numerik siswa. Peran orang tua dalam menyediakan lingkungan belajar mendorong kebiasaan membaca siswa. Kombinasi metode SAS di sekolah dan orang tua secara signifikan meningkatkan kemampuan calistung siswa.